Interplay of chemistry and deformation-induced defects on facilitating topologically-close-packed phase precipitation in nickel-base superalloys. (1st September 2022) - Zhao, Peng; Xie, Guang; Chen, Chunjin; Wang, Xuelu; Zeng, Panlin; Wang, Fang; Zhang, Jian; Du, Kui
Abstract: Topologically close packed (TCP) phases are often formed in nickel-base superalloys with high refractory elements during service, and they are detrimental for the high temperature performance of superalloys. The precipitation process of TCP phases is under scrutiny in particular for deformations that integrate strain and temperature but replicate the working conditions of superalloys. In this work, TCP phase precipitation is studied in nickel-base single crystal superalloys with or without Ru addition under thermomechanical fatigue deformation. Deformation twins on different 111 planes are observed intersecting with each other and forming large number of high angle boundaries. The structure of these high angle boundaries has high similarity to topologically close packed σ phase, and the boundaries are enriched in Re, Ru, Co and Cr, thus it provides both structural origins and constituent elements for the formation of σ phase. Ru is revealed intensely segregating to semi-coherent and incoherent interfaces between TCP phase and the matrix, this reduces the interface energies and leads to a dramatic change of the morphology of TCP phase precipitates. These results provide insight to effects of lattice imperfections and coevolution chemistry on TCP phase formation in superalloys, and shed light on inhomogeneous precipitation in alloys in general. Graphical abstract: Image, graphical abstract